Outlook using environmentally friendly way of preparing of surfaces rolled steel to drawing. - Парусов, Э.В.; Сычков, А.Б.; Губенко, С.И.; Чуйко, И.Н. (Problems of Tribology, 2016)
Parusov E. V., Gubenko S. I., Sychkov A. B., Chuiko I. N. Outlook using environmentally friendly way of preparing of surfaces rolled steel to drawing. The rational temperature of coil formation of rolled steel are identified , which allows to provide the best removability of scale from the metal surface by mechanical means. The relationship between temperature of coil formation and color scale formed on the surface of rolled steel is installed that can serve as a visual assessment of the definition of the metal cooling modes in the conditions of metallurgical enterprises. It is shown that with increasing temperature of formation to 950 … 1000 ºС descaling rolled steel surface to become widely grades can be realized with the use of resource-saving and environmentally friendly mechanical way. High-layout on the coil and then controlled air cooling achieves an effective set of rational structural and mechanical properties rolled steel. The formation of the optimal scale phase composition consisting of wustite , and its ability to remove mechanically way determined by temperature of coil formation, which causes a decrease in steel the SAE 1008 decrease in ductility and increased strength characteristics is founded. The steel SAE 1070 with a decrease in temperature of coil formation appears prohibited normative documents structure of vacation sorbit and the amount of sorbit 1 point decreases. Upon cooling rolled steel from higher temperatures of coil formation due to differential thermal expansion of the metal and slag, dross cracking occurs, with its adhesion to a metal is considerably reduced, allowing further effective to ensure its removal from the surface (до  98 %). Keywords: rolled steel, scale, temperature of coil formation, deformation and heat treatment.